2020
DOI: 10.21743/pjaec/2020.12.37
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Groundwater for Irrigation Using (IWQI) Model, Located in Al-Nimrud Region at Southeastern of Mosul City, Iraq

Abstract: The study aimed to understand the quality of groundwater in Al-Nimrud region south-eastern part of Mosul city, Iraq. Groundwater samples from 10 wells were collected during the dry season and analyzed for their physical and chemical properties using standard laboratory methods. From the analyzed data, some parameters like sodium adsorption ratio (SAR), sodium percentage (Na%), potenial salinity (PS), residual sodium carbonate (RSC), magnesium adsorption ratio (MAR), permeability index (PI) and Kellys ratio (KR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Table (5) shows that the values of SAR, %Na and RSC ranged between (0.40 to 1.600), (12.00 to 25.50) and (-0.20 to -5.50) sequentially. This indicates that there are no problems for SAR, %Na and RSC when this water is used for irrigation (Al-Saffawi et al, 2021b).…”
Section: Materials and Methods: I General Description Of The Current ...mentioning
confidence: 82%
See 2 more Smart Citations
“…Table (5) shows that the values of SAR, %Na and RSC ranged between (0.40 to 1.600), (12.00 to 25.50) and (-0.20 to -5.50) sequentially. This indicates that there are no problems for SAR, %Na and RSC when this water is used for irrigation (Al-Saffawi et al, 2021b).…”
Section: Materials and Methods: I General Description Of The Current ...mentioning
confidence: 82%
“…Sodium and potassium ions using a flame-Photometer (APHA 1998(APHA , 2017. The irrigation parameters were also calculated using the following equations (Xu et al, 2019;Chegbeleh et al, 2020;Al-Saffawi, et al, 2020ab):…”
Section: Materials and Methods: I General Description Of The Current ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, maximum efforts must be focused on building and advancing scientific and service institutions to solve problems of Pollution and waste of water resources, such as building dams on rivers and building water harvesting dams while rationalizing water consumption for all purposes and resolving outstanding problems with upstream countries diplomatically with establishing strong economic relations (AL-SARDAR; AL-SAFFAWI, 2019;SALEH et al 2020;EWAID et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the studies related to assessing the quality of drinking water for livestock and poultry are very few and rare in Iraq, but there are some studies related to this field, including 6 , study to assess the quality of water resources in the Nimrud district, southeast of Mosul city, for watering livestock and poultry using weighted mathematical models. The results of WQI values indicated that 70% of the water samples were of poor-quality water due to the high levels of salts, which amounted to (5069) uS.…”
Section: Introductionmentioning
confidence: 99%